Zlepšili sme starostlivosť o pacientov s artériovou hypertenziou v roku 2021? - Vachulová, Anna; Šimková, Adriana; Filipová, Slavomíra (Vnitrni lekarstvi, 2022)
Arterial hypertension (AH) is a very common disease with increasing incidence and prevalence. AH becomes worldwide the main preventable cause of the preventable deaths. Therefore, it is very important to obtain early diagnose and convenient treatment. Still high cardiovascular mortality in Slovakia, where we have a position at the tail compared to other European countries, very closely related to the failure to obtain treatment blood pressure (BP) target ranges. AH rarely occurs in isolation, and often clusters with other CV risk factors such as dyslipidemia and obesity. 2018 ESC/ESH Guidelines for the management of arterial hypertension has brought several new concepts how to manage arterial hypertension. However, it is important to implement the recommendations of the European Society of Cardiology to everyday clinical practice in each country.
Keywords: Blood Pressure; Blood Pressure Determination; arterial hypertension; měření krevního tlaku; kardiologie; hypertenze; Charter 70/2023; krevní tlak; adherence to treatment; lidé; overweight; Hypertension; antihypertenziva; Antihypertensive Agents; 2018 ESC/ESH Guidelines for the management of arterial hypertension; Cardiology; Humans; obesity